Exploring the decision-making process of female genital cosmetic procedures in Iranian women and constructing and validating a results-based logic model for a healthy public policy: a study protocol - Elham Azmoude; Samira Ebrahimzadeh Zagami; Elahe Hooshmand; Elham Taheri; Nahid Jahani Shoorab (BMC, 2024)
Abstract Background Female genital cosmetic procedures have grown rapidly in most parts of the world. Professional organizations have issued warnings about the complications and long-term consequences of these practices. To be able to adopt the right health policies, it is necessary to know why women decide to perform these procedures. Therefore, the present study will be aim to discover the decision-making process involved in performing female genital cosmetic procedures for Iranian women and construct and validate a results-based logic model for healthy public policy. Methods The present study was conducted in three phases. In the initial phase, a qualitative study will be conducted with the Corbin and Strauss ground theory approach. The participants in the study will be healthy women who desire or have undergone female genital cosmetic procedures without medical indications. In this phase, purposive and theoretical sampling will guide recruitment and data collection. The data will be collected via semi-structured interviews, field notes and observations of individual interactions. The data will be analysed using the approach of Corbin and Strauss (2015). MAXQDA 2007 software was used for managing the process of data analysis. In the second phase, the development of a results-based logic model for a healthy public policy is performed based on the findings of the first phase of the study, interviews with key informants and a review of the results of the literature in this field. Finally, validation of the designed program will be performed by the nominal group technique with the presence of a group of experts in the third phase. Discussion The findings of this study, by identifying women's main concerns related to the studied phenomenon, the existing context, participants' reactions and the consequences of the adopted reactions, can be very important in designing a program that fits Iran's cultural characteristics. In this research, a program using a logical model will be presented that is suitable for policymakers, planners and healthcare service providers to be implemented in the social-cultural context of the study.